Methodology for Managing Financial Resources in Credit Institutions - A. G. Mikheev (Управленческие науки, 2018)
The current state of credit and banking sector is characterized by high competition between credit institutions, taking place in context of increasing business volatility. To maintain competitive advantages, credit institutions have constantly to new conditions - to create new services and products, to continuously enhance efficiency, to introduce innovations. Credit institutions need new, more effective management approaches. Therefore, it is vital to develop new management methods, more flexible than the traditional ones, expanding the capacity of a credit institution to perform financial intermediation between entities of financial and economic activity. It is also important to develop tools, which allow these methods to be applied. To solve the problems under consideration the system approach, fundamental analysis methods, financial mathematics, process control theory and risk theory were used.A methodology has been created for managing financial resources in credit institutions. In accordance with this methodology, the improving efficiency of financial management can be achieved by means of decentralization of financial resources management, the use of a management mechanism based on setting the boundaries of performance indicators and automation of management based on process approach. The process approach based on business-processes, executed in software environment, allows to change rapidly the parameters and schemes of interaction between business-units, and also allows the employees to avoid many routine tasks. The speed of decision-making in the context of centralized management is limited by human factor: much time is spent on making the decision by the hierarchy chain of managers. This problem is solved by delegation of authority to lower-level departments. The use of management, carried out implicitly, by means of changing of performance boundary values and decentralized management mechanism parameters, allows to avoid negative consequences of decentralization, such as possibly uncoordinated actions of a department. The methodology of financial resource management in credit institutions also allows to perform management of the credit institution's business on the account of financial resource distribution by means of transformation of the corresponding business-processes. Currently in Russia there are conditions for implementation of the developed methodology: the credit institutions are automated to a considerable degree and possess both financial and information technologies manpower. The systems based on process approach appeared on the software market. One of such systems - RunaWFE was developed in Russia in the course of this research. Both theoretical basis and technical conditions are ready for the implementation of the developed methodology in Russia.